Phase Error Criterion Based Adaptive Algorithm for Frequency Estimation - Prayuth Inban; Rachu Punchalard; Chawalit Benjangkaprasert (My University, 2024)
A simple phase error criterion (PEC-)-based adaptive algorithm for estimating the frequency of a complex sinusoidal signal in additive white Gaussian and impulsive noises is proposed. The proposed technique makes use of the instantaneous phase response of a first-order complex linear predictor (CLP) as a driving function to update the frequency parameter of the CLP. The proposed PEC is attractive due to its simplicity and high impulsive noise robustness. Theoretical analysis for the mean value of the estimated frequency and the steady-state mean square error (MSE) of the frequency estimate are derived in closed forms. Computer simulations are drawn to show the performance of the proposed frequency estimator.
Keywords: Robustness; Advanced Adaptive Filtering Techniques